2019
DOI: 10.3390/su11154052
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Matters: Consumer Acceptance of Different Vertical Farming Systems

Abstract: Fresh produce within vertical farming systems grows vertically in different layers stacked atop each other, thus allowing for the efficient use of space. As the environment in vertical farming systems is completely controlled, neither sunlight nor soil is necessary. On the one hand, vertical farming may help to provide a healthy diet for the growing global population because it has a greater crop yield per square meter used than conventional farming; moreover, it can offer the opportunity to grow food in clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…The more positive attitude toward purchasing hydroponic, the higher supporting by relatives, and the higher control of purchasing hydroponic, the higher intention to purchase it. When respondents perceived they have control over purchasing hydroponic, it leads to buy the products [41]. In the organic food context, attitude, subjective norm, and perceived behavioral control positively influence purchase intention directly [4,39].…”
Section: Discussionmentioning
confidence: 99%
“…The more positive attitude toward purchasing hydroponic, the higher supporting by relatives, and the higher control of purchasing hydroponic, the higher intention to purchase it. When respondents perceived they have control over purchasing hydroponic, it leads to buy the products [41]. In the organic food context, attitude, subjective norm, and perceived behavioral control positively influence purchase intention directly [4,39].…”
Section: Discussionmentioning
confidence: 99%
“…Naturalness seems to be a high influencing indicator for consumers' selection globally as also a critical significant factor on the usefulness of the agricultural system. According to Jürkenbeck et al (2019) , customers replied that LED lighting is not considered a too artificial tool for horticulture and slightly agreed that they do not consider indoor vertical farming too artificial concerning the overall production system. Even if consumers in general prefer naturally and traditionally produced food, nevertheless the fact that food of indoor vertical farms grow without chemical additives is highly considered.…”
Section: Customer Opinion On Indoor Vertical Farmsmentioning
confidence: 99%
“…On the other hand, under a customer research conducted by Jürkenbeck et al (2019) , it is noticed that consumers seem to present a high acceptance on indoor vertical farming concerning the offering sustainability and the high ecological footprint. People seem to select their purchased food based on their concerns on the naturalness, ethics and environmental status.…”
Section: Customer Opinion On Indoor Vertical Farmsmentioning
confidence: 99%
“…In addition, consumer acceptance of vertically produced vegetables should also be evaluated. A study conducted by Jürkenbeck, Heumann, and Spiller (2019) reported that there were 2 factors, namely sustainability and naturalness of the produce, affecting consumer acceptability. Most of the people surveyed were not aware of what vertical farming is.…”
Section: Urban Farmingmentioning
confidence: 99%